Influence of expertise level on techniques of applying top and back spins in cue sports - Pan, J. W.; Komar, J.; Yang, C.; Kong, P. W. (Sports Biomechanics, 2022)
This study compared the kinematics of upper body and cue stick among players of various skill levels when performing back spin and top spin shots. Twenty-eight male cue sports players were assigned to the novice (n = 10), intermediate (n = 9), or skilled groups (n = 9). The back spin and top spin tests were administrated while kinematic data were recorded using a 3D motion capture system. The results revealed greater upper limb joint ranges of motions (all p < 0.05), maximum angular velocities (all p < 0.05), and cue tip speed in the back spin than top spin shots (p < 0.001). None of joint kinematic or shot performance variables investigated was significantly different among the three skill levels (all p > 0.05). For the head movement, the novice group exhibited greater anteroposterior displacement than the skilled group (p = 0.020). In conclusion, except for the head movement, the upper body and cue stick kinematics did not significantly differ among players with varied skill levels. Greater joint ranges of motions and angular velocities were required to generate a faster cue tip speed for the back spin shots when compared with the top spin shots.